Increasing seated reaction forces with lower body negative pressure - Suhas Rao Velichala; Jonathan Kim; Alan R. Hargens (npj Microgravity)
Abstract This study evaluates ground reaction forces and cardiovascular responses during seated lower body negative pressure (LBNP). Ten healthy subjects were exposed to randomized LBNP levels (−10 to −40 mmHg) while seated in a sealed chamber. Gluteal, foot, and total reaction forces, along with heart rate and blood pressure, were measured at each level. Reaction forces increased significantly with rising LBNP (P < 0.05), exceeding baseline at 10 mmHg and doubling by 30 mmHg. Cardiovascular parameters remained stable, indicating no acute hemodynamic risk. Force generation was dependent on LBNP amplitude and waist cross-sectional area. These findings suggest that seated LBNP is a safe and effective method to simulate Earth-like seated posture in microgravity, offering a promising countermeasure to mitigate musculoskeletal deconditioning and support gravitational adaptation during long-duration spaceflight.